Microbiological safety aspects of mangoes (Mangifera indica) and papayas (Carica papaya): a mini-review | Aspectos de segurança microbiológica de manga (Mangifera indica) e papaya (Carica papaya): mini revisão - Ana Lúcia Penteado (Fundação Oswaldo Cruz (FIOCRUZ), 2017)
This review describes several aspects related to microbiological safety in mangoes and papayas, such as incidence, outbreaks, internalisation and growth/survival of bacterial pathogens. Mangoes and papayas are often served sliced in food establishments in fresh pieces at salad bars, deli counters and as pulp juice. In general, these products do not undergo any process to eliminate pathogenic microorganisms before consumption, and a long shelf life could theoretically provide time for these microorganisms to multiply without affecting the organoleptic qualities of the fruit, thereby increasing the risks of food-borne illness. The data presented in this review show that low temperatures can impede microbial growth, but not completely inhibit such growth in mangoes and papayas. Highest growth rates were observed in the range between 22 and 37oC. In the last 20 years, several outbreaks of salmonellosis caused by these fruits or by food made with these fruits have been reported. The control of the temperature in the fruit washing water is important to prevent the internalisation of Salmonella spp. The implementation of strategies such as Good Agricultural Practices, Good Manufacturing Practices and Hazard Analysis Critical is important, as these methods can eliminate or significantly reduce microbial contamination. ================================================== Esta revisão descreve diversos aspectos relacionados à segurança microbiológica em manga e mamão papaya como; incidência, surtos, internalização e crescimento/sobrevivência de patógenos bacterianos nestas frutas. Mangas e papayas são frequentemente servidas fatiadas em estabelecimentos alimentícios como pedaços frescos, em misturas para saladas, expostas em balcões e como polpas de frutas. No geral, estes produtos não passam por qualquer processo para eliminar microrganismos patogênicos antes do seu consumo e uma vida longa de prateleira poderia teoricamente fornecer tempo para que estes microrganismos se multipliquem sem afetar as qualidades organolépticas destas frutas e assim aumentar o risco de doenças de origem alimentar. Os dados apresentados nesta revisão mostram que baixas temperaturas podem diminuir o crescimento de microrganismos mas não inibi-los em mangas e papayas. Os melhores crescimentos foram observados na faixa de 22-37oC. Nos últimos 20 anos diversos surtos de salmonelose nestas frutas ou produtos feitos com as mesmas foram relatados. O controle da temperatura da água de lavagem de frutas é importante para prevenir a internalização de Salmonella spp. A implementação de estratégias como Boas Práticas Agrícolas, Boas Práticas de Produção e Análise Crítica de Pontos de Controle são importantes já que podem eliminar ou reduzir significantemente a contaminação microbiana.